2010
DOI: 10.1016/j.ydbio.2009.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Myoblast fusion: When it takes more to make one

Abstract: Cell-cell fusion is a crucial and highly regulated event in the genesis of both form and function of many tissues. One particular type of cell fusion, myoblast fusion, is a key cellular process that shapes both the formation and repair of muscle. Despite its importance for human health, the mechanisms underlying this process are still not well understood. The purpose of this review is to highlight the recent literature pertaining to myoblast fusion and to focus on a comparison of these studies across several m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
206
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(209 citation statements)
references
References 179 publications
(343 reference statements)
3
206
0
Order By: Relevance
“…Furthermore, we have determined that SLK is capable of localizing with paxillin (Figure 3.1), a focal adhesion protein that has also been implicated in the regulation of adhesion turnover, to the leading edge and membrane ruffle of migrating cells [78,99,107,120]. Since SLK is required for fusion in C2C12, a process whereby coordinated migration signaling is required for the alignment and formation of myoblasts into myotubes, we tested for, and observed that SLK is capable of co-localizing with paxillin in differentiating myoblasts (Figure 3.1) [129,130].…”
Section: Slk Phosphorylates Paxillin In Vitromentioning
confidence: 99%
“…Furthermore, we have determined that SLK is capable of localizing with paxillin (Figure 3.1), a focal adhesion protein that has also been implicated in the regulation of adhesion turnover, to the leading edge and membrane ruffle of migrating cells [78,99,107,120]. Since SLK is required for fusion in C2C12, a process whereby coordinated migration signaling is required for the alignment and formation of myoblasts into myotubes, we tested for, and observed that SLK is capable of co-localizing with paxillin in differentiating myoblasts (Figure 3.1) [129,130].…”
Section: Slk Phosphorylates Paxillin In Vitromentioning
confidence: 99%
“…4 Thus, the controlled alignment of myoblasts and myotubes in vitro could have significant application clinically, as it is a crucial step in myofibrillogenesis. [5][6][7][8] Furthermore, it has been shown that myoblast adhesion and the subsequent formation of myotubes in vitro are sensitive to microstructured topography [9][10][11] as well as to the biochemical cues presented as micropatterned areas of ECM proteins. 12 Mechanical tension and stretching can also contribute to myoblast alignment, fusion, and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The unique identity of each muscle fiber is conferred through overlapping signaling pathways and cell autonomous transcription factors that specify muscle progenitors Baylies et al 1998;Frasch 1999;Tixier et al 2010), which then undergo asymmetric cell division to generate founder cells (FCs) (Bate 1990;Carmena et al 1998). A single FC initiates the formation of multinucleate syncytia by fusing with fusion competent myoblasts (FCMs) (Rochlin et al 2010;Abmayr and Pavlath 2012). FCs dictate the number of cell fusion events that take place, leading to a characteristic number of nuclei for each muscle in the pattern .…”
mentioning
confidence: 99%